Ag-catalyzed diastereoselective [6 + 3] cycloaddition of tropone with homoserine lactone-derived azomethine ylides: synthesis of tricyclic spiropiperidines. Issue 77 (2nd August 2016) - Wu, Yang; Liu, Honglei; Zhang, Lei; Sun, Zhanhu; Xiao, Yumei; Huang, Jiaxing; Wang, Min; Guo, Hongchao
Abstract : Ag-catalyzed [6 + 3] cycloaddition of tropone with homoserine lactone derived azomethine ylides has been developed. Abstract : Ag-catalyzed [6 + 3] cycloaddition of tropone with homoserine lactone derived azomethine ylides has been developed. The reaction works efficiently under mild conditions to give tricyclic spiropiperidines in moderate to excellent yields with excellent diastereoselectivities.